Neuroimaging Manifestations and Clinical Correlates of Japanese Encephalitis: Insights from an MRI Case Series - Hussain, Ameer; Rubben, Ajay Lucas; Raj, Vishnu (Journal of clinical and diagnostic research, 2024)
Japanese Encephalitis (JE) poses a significant public health threat across Asia and the Western Pacific, leading to considerable mortality and morbidity if not promptly diagnosed and treated. This flaviviral infection, transmitted by Culex mosquitoes, primarily affects children but can impact individuals of all ages. Prompt diagnosis relies on detecting Japanese Encephalitis Virus (JEV) IgM antibodies in serum or Cerebrospinal Fluid (CSF), alongside characteristic Magnetic Resonance Imaging (MRI) findings. In this MRI case series, three confirmed cases of JE are presented, showcasing the typical neuroimaging manifestations observed in affected individuals. All cases exhibited bilateral thalamic hyperintensities on T2-weighted and Fluid Attenuated Inversion Recovery (FLAIR) images, a hallmark feature of JE. Additionally, one patient demonstrated involvement of the substantia nigra and bilateral frontal cortex. The clinical implications of present study findings underscore the importance of considering JE as a differential diagnosis in patients presenting with symptoms of encephalitis, especially when MRI reveals bi-thalamic signal alterations. Early recognition and initiation of appropriate treatment, including antiviral agents, are crucial for improving outcomes and reducing mortality. This study contributes to the existing literature by reinforcing the importance of neuroimaging in diagnosing JE and highlighting the distinct MRI patterns associated with the disease. Recognising these characteristic imaging features can aid clinicians in promptly identifying and managing JE cases, thereby mitigating the associated morbidity and mortality.